Seals and Sealing in the Administration of the State: A Functional Analysis of Seals in Second Millennium B.C. Syria - Magness-Gardiner, Bonnie Sue (2012)
Ph.D. Dissertation; Supervisors: William G. Dever and Norman Yoffee. Order No. DA8727931; DissAbstr 48/09 (March 1988) 2369-A. [This study incorporates both archaeological and textual information from Mari, Alalah, and U